Identification of ksg1 mutation showing long‐lived phenotype in fission yeast. (26th September 2021) - Matsui, Kotaro; Okamoto, Keisuke; Hasegawa, Tomoka; Ohtsuka, Hokuto; Shimasaki, Takafumi; Ihara, Kunio; Goto, Yuhei; Aoki, Kazuhiro; Aiba, Hirofumi
Abstract: Fission yeast is a good model organism for the study of lifespan. To elucidate the mechanism, we screened for long‐lived mutants. We found a nonsense mutation in the ksg 1 + gene, which encodes an ortholog of mammalian PDK1 (phosphoinositide‐dependent protein kinase). The mutation was in the PH domain of Ksg1 and caused defect in membrane localization and protein stability. Analysis of the ksg1 mutant revealed that the reduced amounts and/or activity of the Ksg1 protein are responsible for the increased lifespan. Ksg1 is essential for growth and known to phosphorylate multiple substrates, but the substrate responsible for the long‐lived phenotype of ksg1 mutation is not yet known. Genetic analysis showed that deletion of pck2 suppressed the long‐lived phenotype of ksg1 mutant, suggesting that Pck2 might be involved in the lifespan extension caused by ksg1 mutation. Abstract : Chronological lifespan is extended by ksg1‐3 mutation in fission yeast. After screening for long‐lived mutants, we found a ksg1‐3 mutant which has a nonsense mutation in the PH domain of the Ksg1 protein. This mutation was suggested to cause loss of membrane localization of Ksg1 protein as well as a decrease in protein amounts based on the Ksg1(1–539)‐tag fusion analysis. We propose that the long‐lived phenotype is not due to loss of membrane localization, but to the decrease in protein amounts.